Alterações bioquímico-fisiológicas em pacu (Piaractus mesopotamicus Holmberg 1887) exposto a um inseticida à base de deltametrina - Rossi, Priscila Adriana (2013)
The use of insecticides is increasing not only for agriculture purposes but also against threats to public health caused by insects. However, in the last few years it is possible to see a frequent replacement of current pesticides for new others, which differ in toxicity. Pyrethroid insecticides, deltamethrin is an example, are considered ideal xenobiotics due to low toxicity to mammals and birds, a wide range of targets and no biomagnification. Nevertheless, several studies report the toxic effects of deltamethrin on non-target organisms, such as fishes. In this vertebrate group, high toxicity seems to be due to an enzymatic deficiency in hydrolyzing pyrethroids and this fact can be assessed through hematologic, metabolic, neurologic, and oxidative stress investigations. Pacu, Piaractus mesopotamicus, is a freshwater fish from South America and is affected by massive use of pyrethroids. This species is widely known in the Midwest region of Brazil, wherein the largest agrochemicals use takes place. The aim of this study was the acute toxicity determination of deltamethrin (LC(I)50;48h) for pacu juveniles; evaluation of hematologic, metabolic and antioxidant defenses of pacu after 96 h of sublethal exposure to deltamethrin (10% LC(I)50;48h); evaluation of deltamethrin effects on the brain acetylcholinesterase (AChE) in vivo. The LC(I)50;48h estimated to deltamethrin in pacu juveniles was 17.32 μg L-1. In response to sublethal exposure, pacu depicted blood changes suggestive of erythropenia and dehydration. Metabolic changes included hepatic glycogenolysis, muscle proteolysis, and hyperglycemia, suggesting an overload of the energetic metabolism to serve the detoxification processes. Regarding antioxidant defenses, the occurrence of hepatic lipid peroxidation is indicative of oxidative stress with depletion of non-enzymatic antioxidants and alterations in antioxidant enzymes activity. Also, deltamethrin depicted AChE inhibition in fish exposed to sublethal concentrations.